Cultural impediments to frank communication regarding end-of-life care between older nursing home residents and their family members in Taiwan: a qualitative study - Hsin-Tzu Sophie Lee; Chia-Ling Yang; Sei-Ven Leu; Wen-Yu Hu (BMC, 2022)
Abstract Background When older nursing home residents and their families are faced with end-of-life care decisions in Taiwan, they make them in the context of traditional cultural norms and socioeconomic changes. Both parties (residents and their family members) are often unwilling to broach the topic, leading to a decisional impasse. The aim of this study was to understand difficult-to-raise issues related to end-of-life care by investigating the perspectives of older nursing home residents and their family members. Methods This qualitative descriptive study was conducted using content analysis based on the Consolidated Criteria for Reporting Qualitative Research. Purposive sampling was used to select the participants, and sampling continued until data saturation. Data were collected using semi structured interviews, and related analyses were conducted using an inductive approach. Results Ten residents and twelve family members were interviewed individually. Six main themes were identified: (1) the inevitability of a goodbye; (2) a good death; (3) going with or against traditional culture; (4) better a good death than a bad life; (5) abiding by the residents' decisions; and (6) being willing but unable to take care of residents. Conclusion Nursing home residents and their family members' thoughts on end-of-life care shifted toward the concept of a good death, and they even regarded death as a form of liberation. Health care providers may serve as mediators to counsel a resident and their family members separately, enabling them to speak up and understand each other's thoughts on end-of-life care before a decision is made so that neither party has regrets.